2022
DOI: 10.1021/acs.jpcc.2c01842
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cu(I)-5-nitropyridine-2-thiol Cluster with NIR Emission: Structural and Photophysical Characterization

Abstract: A novel Cu(I) cluster compound has been synthesized by reacting CuI with the 2,2′-dithiobis(5-nitropyridine) ligand under solvothermal conditions. During the reaction, the original ligand breaks into the 5-nitropyridine-2-thiolate moiety, which acts as the coordinating ligand with both N- and S-sites, leading to a distorted octahedral Cu 6 S 6 cluster. The structure has been determined by single-crystal X-ray diffraction and FT-IR analysis, and the photophysical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…One of the most studied and fascinating properties of metal nanoclusters is their photoluminescence, which can be applied in sensing, biological imaging, and optical devices. , Cu­(I) complexes are well known as good luminescent materials. , The emission peaks of the Cu­(I) complexes always lie in the visible range because of their d 10 electronic structures and favorable low-energy ligand-to-metal charge transfer or cluster-centered transition. The extension of the emission wavelength from the first near-infrared (750–950 nm, NIR-I) to the second near-infrared (1000–1700 nm, NIR-II) window is beneficial to deeper tissue imaging and reduced photon scattering when applied in bioimaging and thus is highly desirable but hard to be accessible. Several copper clusters were reported to have emissions in the near-infrared (NIR) region. [Cu 15 ( t BuCC) 14 NO 3 ] featured a board NIR emission band centered at 871 nm, which is, to the best of our knowledge, the longest emission wavelength of all atomically precise copper clusters . While gold, silver, and alloy nanoclusters have been demonstrated to possess NIR-II emissions, as cheaper congeners, there are no NIR-II emissive copper nanoclusters being reported yet …”
Section: Introductionmentioning
confidence: 91%
“…One of the most studied and fascinating properties of metal nanoclusters is their photoluminescence, which can be applied in sensing, biological imaging, and optical devices. , Cu­(I) complexes are well known as good luminescent materials. , The emission peaks of the Cu­(I) complexes always lie in the visible range because of their d 10 electronic structures and favorable low-energy ligand-to-metal charge transfer or cluster-centered transition. The extension of the emission wavelength from the first near-infrared (750–950 nm, NIR-I) to the second near-infrared (1000–1700 nm, NIR-II) window is beneficial to deeper tissue imaging and reduced photon scattering when applied in bioimaging and thus is highly desirable but hard to be accessible. Several copper clusters were reported to have emissions in the near-infrared (NIR) region. [Cu 15 ( t BuCC) 14 NO 3 ] featured a board NIR emission band centered at 871 nm, which is, to the best of our knowledge, the longest emission wavelength of all atomically precise copper clusters . While gold, silver, and alloy nanoclusters have been demonstrated to possess NIR-II emissions, as cheaper congeners, there are no NIR-II emissive copper nanoclusters being reported yet …”
Section: Introductionmentioning
confidence: 91%
“…237 A distorted octahedral Cu 6 kernel stabilized by rigid and multiple coordination structures was found that had strong red room-temperature phosphorescence with a maximum at about 765 nm. 298 The emission spectrum sharpened and further red-shifted at 77 K, exhibiting a band at 815 nm. To achieve large electronic delocalization, 299 a heterometallic Au 11 @Cu 1 cluster was prepared that showed up-converted anti-Stokes fluorescence and phosphorescence.…”
Section: Transition Metal Complexationmentioning
confidence: 97%
“…The ultimate kernel size is likely located within single-atom scale, which would permit simpler yet more efficient alterations of electronic radiative and nonradiative processes . A distorted octahedral Cu 6 kernel stabilized by rigid and multiple coordination structures was found that had strong red room-temperature phosphorescence with a maximum at about 765 nm . The emission spectrum sharpened and further red-shifted at 77 K, exhibiting a band at 815 nm.…”
Section: Synthesis Strategies Of Room-temperature Phosphorescence In ...mentioning
confidence: 99%
“…The metal nanoclusters that emit in the near-infrared (NIR > 750 nm) region are attracting increasing attention for their potential applications in optoelectronics, sensors, and telecommunications. Their atomically precise geometric structures and well-defined compositions offer ideal platforms for understanding the relationship between structure and photoluminescence (PL). Considerable advancements in the PL mechanism and applications of NIR-emissive gold and silver nanoclusters have been made in the past decades. Nevertheless, as their lighter congeners, the synthesis of copper nanoclusters (Cu NCs) encounters formidable challenges, primarily attributed to their inherent poor stability, not to mention the investigations on their NIR PL. So far, only very few Cu NCs have been discovered to emit in the NIR region under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%